A Study of Static Performance of Fixed Inclined Slider Bearings – A Power Law Model - MH Oladeinde; RO Edokpia; AI Unuigbe (Journal of Applied Sciences and Environmental Management)
In this paper, the performance of a fixed inclined slider bearing whose surfaces are lubricated by a non Newtonian power law lubricant is investigated numerically. Based on the power law model, the modified Reynolds equation is derived and solved using the finite element method. The effect of flow index on pressure distribution, load capacity, maximum pressure is presented graphically. @JASEM